Pengaruh Model Pembelajaran Kontekstual Berbasis Etnososial Terhadap Hasil Belajar Siswa Pada IPAS Materi Norma Dalam Adat Istiadat Di Daerahku - Muthoharoh, Aswajum; Siswoyo, Andika Adinanda (JOURNAL OF EDUCATION FOR ALL, 2024)
This study stems from the lack of learning outcomes in social sciences, particularly in the social context related to customs and culture in grade 4 at UPTD SDN Tanjungjati 2. The process of linking culture to learning was fixated on textbooks, and a comprehensive learning model had not been implemented. Based on these problems, a solution was provided in the form of an ethnosocial-based contextual learning model. The contextual learning model is a model that enables students to relate learning to real-life situations. Ethnosocial integrates local wisdom values in the social aspect into learning. The purpose of this study is to determine the influence of the contextual learning model on students' learning outcomes in the material of norms in local customs. The research design used is pre-experimental design with the type one-group pretest-posttest design. The sampling technique used was saturated sampling, with a total sample of 18 people. The instrument used consisted of 10 multiple-choice questions for both the pretest and posttest. The results of the Wilcoxon hypothesis test with a significance level of 5% were 0.000, meaning 0.000 < 0.05, thus H0 is rejected and H1 is accepted. There is an influence of the ethnosocial-based contextual learning model on students' learning outcomes in social sciences on the material of norms in local customs.